2021
DOI: 10.21037/atm-21-5169
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of sentinel lymph node biopsy and non-sentinel lymph node metastasis in invasive ductal and invasive lobular breast cancer: a nationwide cross-sectional study (CSBrS-001)

Abstract: Background: Information regarding the implementation of sentinel lymph node biopsy (SLNB) in invasive lobular carcinoma (ILC) is scarce, and whether ILC patients with 1-2 positive sentinel lymph nodes (SLNs) can be omitted from axillary lymph node dissection (ALND) remains controversial. This study aimed to compare involvement of SLNs and non-SLNs between patients with invasive ductal carcinoma (IDC) and ILC.Methods: We retrospectively collected the clinical and pathological data of invasive breast cancer pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Zhang et al reported a higher incidence of metastasis in non-SLNs for ILC compared to IDC among patients with 1-2 positive SLNs. However, the difference was insigni cant (45.4% in ILC, n = 30 vs. 34, 8% in IDC, n = 1,122, P = 0.366) (30). Therefore, surgeons should be more cautious in omitting ALND for ILC patients with 1-2 positive SLNs.…”
Section: Discussionmentioning
confidence: 96%
“…Zhang et al reported a higher incidence of metastasis in non-SLNs for ILC compared to IDC among patients with 1-2 positive SLNs. However, the difference was insigni cant (45.4% in ILC, n = 30 vs. 34, 8% in IDC, n = 1,122, P = 0.366) (30). Therefore, surgeons should be more cautious in omitting ALND for ILC patients with 1-2 positive SLNs.…”
Section: Discussionmentioning
confidence: 96%
“…Zhang et al reported a higher incidence of metastasis in non-SLNs for ILC compared to IDC among patients with 1–2 positive SLNs. However, the difference was not significant (45.4% in ILC, n = 30 vs. 34, 8% in IDC, n = 1,122, P = 0.366) [ 30 ]. Therefore, surgeons should be more cautious in omitting ALND for ILC patients with 1–2 positive SLNs.…”
Section: Discussionmentioning
confidence: 99%
“…There exist conflicting data regarding whether lobular histology is linked to a higher risk of involvement in non-SLNs [75][76][77][78][79]. However, the overall node positivity rate between invasive ductal carcinoma and ILC has not been shown to be significantly different in several studies [80][81][82][83][84].…”
Section: Invasive Lobular Carcinoma Settingmentioning
confidence: 99%